(untitled) (Economic and Political Thought, 2016)
The purpose of this article is an empirical analysis of the evolution of national fiscal rules in the European Union countries in the years 2004–2014. Fiscal rules are some of the most important factors affecting the efficiency of fiscal policy carried out in a country. During the economic crisis, the primary objective of fiscal rules is to consolidate public finance, most of all to reduce budget deficit and public debt. The study focuses on the assessment of changes in the number of national fiscal rules as well as changes in their quality in the 27 old and new EU countries. It is assumed that the most important factors differentiating the average number of national fiscal rules applied in particular countries are: the length of the country’s membership in the EU, the fiscal mentality of a country, and use of the single currency. The empirical research shows that in the period 2004–2014 the number of national fiscal rules in the EU was systematically growing, and their quality was improving dynamically. Moreover, it occurred that the above-mentioned factors are statistically significant determinants of the number of national fiscal rules applied by different EU countries.